2017
DOI: 10.1016/j.bjm.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Pseudomonas aeruginosa : association with virulence genes and biofilm formation

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes frequently nosocomial infections, currently becoming more difficult to treat due to the various resistance mechanisms and different virulence factors. The purpose of this study was to determine the risk factors independently associated with the development of bacteremia by carbapenem-resistant P. aeruginosa, the frequency of virulence genes in metallo-β-lactamases producers and to evaluate their ability to produce biofilm. We conducted a case–cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 42 publications
7
42
2
4
Order By: Relevance
“…Ding et al [ 25 ] in a Meta-analyses of 50 studies published from 2010 to 2014 investigated antimicrobial-resistant P. aeruginosa and reported the varied prevalence of resistance, with high levels of resistance to gentamicin. Gonçalves et al [ 26 ] reported that 73.9% of P. aeruginosa were multidrug-resistant and 43.9% were resistant to carbapenems. Khosravi et al also found high-level resistance to gentamicin, ciprofloxacin, meropenem, piperacillin/tazobactam and imipenem, and no resistance to colistin among P. aeruginosa strains isolated from burn patients in a burn center of Ahvaz; Southeast of Iran [ 27 ].…”
Section: Main Textmentioning
confidence: 99%
“…Ding et al [ 25 ] in a Meta-analyses of 50 studies published from 2010 to 2014 investigated antimicrobial-resistant P. aeruginosa and reported the varied prevalence of resistance, with high levels of resistance to gentamicin. Gonçalves et al [ 26 ] reported that 73.9% of P. aeruginosa were multidrug-resistant and 43.9% were resistant to carbapenems. Khosravi et al also found high-level resistance to gentamicin, ciprofloxacin, meropenem, piperacillin/tazobactam and imipenem, and no resistance to colistin among P. aeruginosa strains isolated from burn patients in a burn center of Ahvaz; Southeast of Iran [ 27 ].…”
Section: Main Textmentioning
confidence: 99%
“…Hospitais oncológicos figuram como áreas de alto risco para aquisição de infeções considerando: tempo de internação, a utilização de imunossupressores e/ou antibióticos, procedimentos invasivos (intubação traqueal, cateterização venosa central, sondagem vesical, e outros), doença de base concomitante, condições nutricionais, extremos de idade, dentre outros aspectos 11,12,13,14,15 .…”
unclassified
“…Moreover, they reported that isolates of burn infection had the highest frequency of virulence genes. Gonçalves et al (2017) also reported the biofilm producing P. aeruginosa isolated from clinical samples in Brazil and most of the strains were found to be positive for aprA, plcH, plcN, lasA, lasB and toxA genes which can further contribute to a worse prognosis associated with severe infections.…”
Section: Detection Of Biofilm Associated Genes Virulence Genes and Amentioning
confidence: 96%